Anti-inflammatory potential of black cumin seed oil and its nanoemulsion formulation against lipopolysaccharide-induced liver injury in mice - Hesham Haffez; Rehab Hosni; Shady A. Swidan; Hatem K. Amin (Asian Pacific Journal of Tropical Biomedicine)
Objective: To evaluate the anti-inflammatory effect of black cumin seed oil (BCSO) and its nanoemulsion on lipopolysaccharide (LPS)-induced liver injury in mice. Methods: LPS-induced acute liver injury mouse model was used to evaluate the effects of BCSO and its nanoemulsion formulation on liver function. Hepatic inflammatory markers including Toll-like receptor 4 (TLR4), interleukin(IL)-1β, heme-oxygenase 1, BAX, and BCL-2 were assessed using real-time PCR. Additionally, protein levels of reduced glutathione, tumor necrosis factor-α, and IL-6 were measured using ELISA, and histological analysis was performed. Indomethacin was used as a standard positive control for comparison. Results: BCSO reduced LPS-induced liver injury and exhibited strong anti-inflammatory effects by downregulating the expression of TLR4, IL-1β, IL-6, tumor necrosis factor-α, and heme-oxygenase 1. Additionally, BCSO demonstrated antioxidant properties by increasing reduced glutathione protein levels and decreasing key apoptotic markers BAX and BCL-2 in hepatocytes. The nanoemulsion formulation further enhanced these anti-inflammatory, antioxidant, and anti-apoptotic effects, and histological examination confirmed this effect. Combining BCSO with indomethacin at a lower dose improved efficacy, thereby reducing its potential side effects. Conclusions: The investigation reveals the anti-inflammatory impact of BCSO and its nanoemulsion formulation on LPS-induced liver oxidative stress, inflammation, and apoptosis.